PENGARUH EXPERIENTAL MARKETING DAN BRAND TRUST TERHADAP LOYALITAS PELANGGAN (STUDI PADA RM. PAK DATUK KOTA DUMAI) - Yani, Ulfa; Karneli, Okta (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This study aims to determine how much influence of experiental marketing and brand trust of the customer loyalty on RM. Pak Datuk Dumai. Samples in this study were taken as many as 100 respondents and techniques used Accidental Sampling. The data in this study using survey methods through questionnaires filled by consumers. Data obtained from the results of questionnaires and then processed to then tested by statistics by SPSS program. The results of analysis using simple linear regression analysis, multiple linear regression analysis, determination test (R2), individual significance test (t test), and simultaneous significant test (Test F) so that it can be seen that experiental marketing, variables influence customer loyalty variable and brand trust variable influence to customer loyalty variable. Experiental marketing variable and brand trust variable influence simultaneously to customer loyalty. The calculation results are known R square is the coefficient of determination and obtained R Squarevalue of 0,199. That is, experiental marketing and brand trust affects to customer loyalty by 19,9%.Keywords: Experiental Marketing, Brand Trust and customer loyalty